Strategi Kepala Sekolah dalam Mengembangkan Sarana Pendidikan di MTSN 2 Cirebon - Nur Alifah, Nur Alifah - (JIEM (Journal of Islamic Education Management), 2021)
ABSTRACTThe problem of educational facilities is basically complex. Schools are required to have independence to regulate and manage the interest of the school. According to their own needs and abilities and based on quality, aspirations and participation of school resident continue to refer to applicable national education laws  and  regulations.  The  principal  as  a  leader  plays  an  important  role  in managing the facilities at the school in order to support  his learning activitie s at school. For this reason this research was conducted, explaining the importance of the  participal’s  role  and  the  principal’s  strategy  in  developing  educational facilities. This research in based on the SISDIKNAS law and corcerned theory. Research approach using qualitative research. Data collection techniques though participant observation, in-depth interviews and documentations. Technical analysis of qualitative data through data reduction, data presentation and conclusion drawing. Based on the results of the research that : 1) The principal has done his part in developing education facilities in MTs Negeri 2 Cirebon City.2) The strategy under taken by school principals in developing educational facilities is by forming special taems, collaborations with other institutions or againcies. 3) The inhibiting factor for school principals in developing educational facilities is the length of disbursement of funds from the goverment, while supporting factors for school principals in developing educational facilities is the incomplete facilities available in schools to support learning activities.Keywords: Strategy, Principal, Education facilities.  ABSTRAKMasalah sarana pendidikan pada dasarnya cukup kompleks. Sekolah dituntut  memiliki  kemandirian  untuk  mengatur  dan  mengurus  kepentingan sekolah menurut kebutuhan dan kemampuan sendiri serta berdasarkan mutu, aspirasi dan partisipasi warga sekolah tetap mengacu pada peraturan dan perundang-undangan pendidikan nasional yang berlaku. Kepala sekolah sebagai pemimpin,  berperan  penting  dalam  mengelola  sarana  yang  terdapat  disekolah demi menunjangnya kegiatan pembelajaran disekolah.Untuk itulah penelitian ini dilakukan, memaparkan pentingnya peran kepala sekolah dan strategi kepala sekolah dalam mengembangkan sarana pendidikan. Penelitian ini didasarkan pada undang-undang sisdiknas dan teori prihatin. Pendekatan penelitian menggunakan penelitian kualitatif. Teknik pengumpulan data melalui obserfasi partisipan, wawancara mendalam  dan  dokumentasi. Teknis analisi  data  kualitatif  melalui reduksi data, penyajian data dan penarikan kesimpulan. Berdasarkan hasil penelitian bahwa: 1) kepala sekolah sudah melakukan peranannya dalam mengembangkan sarana pendidikan di MTs Negeri 2 Kota Cirebon. 2) Strategi yang dilakukan kepala sekolah dalam mengembangkan sarana pendidikan yaitu dengan  cara membentuk  tim  khusus,  kerjasama  dengan  komite  sekolah,   dan kerjasama  dengan  lembaga  atau  instansi  lain.  3)  Faktor  penghambat  kepala sekolah  dalam  mengembangkan  sarana  pendidikan  yaitu  lamanya  pencairan dana dari pemerintah, sedangkan faktor pendukung kepala sekolah dalam mengembangkan  sarana  pendidikan  yaitu  belum  lengkapnya  fasilitas  yang terdapat disekolah untuk menunjang kegiatan pembelajaran.Kata Kunci: Strategi, Kepala Sekolah, Sarana Pendidikan.